The interface of cognitive and industrial, work and organizational psychology - Hodgkinson, Gerard P. (Journal of occupational and organizational psychology, 2003)
This special issue brings together a collection of papers that variously integrate, extend and/or test new theory and research lying at the boundaries of the cognitive sciences and the field of industrial, work and organizational (IWO) psychology. Over the last two decades, the IWO psychology field in general has witnessed a dramatic upsurge in the development and testing of theories of work‐related behaviour and the design of interventions with a cognitive emphasis. In the related areas of engineering psychology and ergonomics, for example, researchers have devoted considerable attention to an analysis of the nature and significance of employees' mental models of complex operating systems in terms of their impact on system performance while in the area of selection and assessment, attribution theory and other work from the field of social cognition have increasingly informed the analysis of personnel selection interviews. Cognitive theory and research have also been applied in an attempt to better understand the underlying bases of appraisers' judgments in the appraisal of performance. In the area of training and development, conventional approaches to the analysis, design, and evaluation of interventions are being augmented, and in some cases openly challenged, by the application of cognitive constructs, theories, and principles. Much recent theory and research relating to the topics of employee relations and motivation, organizational development and change, teamwork, leadership, organizational culture and climate, negotiation, group decision‐making, stress, and personality and individual differences has also been decidedly cognitive in emphasis. This essay provides a selective overview of these developments, both in order to place in context the other contributions to this volume and in order to reflect more generally on the state of theory and research lying at the IWO‐cognitive psychology interface.